2022
DOI: 10.1002/hbm.25841
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of superior frontal gyrus cortical thickness and resting‐state functional connectivity in abstinent heroin users after 8 months of follow‐up

Abstract: Compared with healthy controls, heroin users (HUs) show evidence of structural and functional brain alterations. However, little is known about the possibility of brain recovery after protracted heroin abstinence. The purpose of this study was to investigate whether brain recovery is possible after protracted abstinence in HUs. A total of 108 subjects with heroin addiction completed structural and functional scans, and 61 of those subjects completed 8-month follow-up scans. Resting-state data and 3D-T1 MR imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…Although great progress had been made, abnormal functional connections in these networks in heroin users (HUs) were very limited. Moreover, brain regional and circuit-level recovery after prolonged abstinence had been observed in previous addiction studies [ 9 , 13 ]. Less is known about whether the brain recovery phenomenon in large-scale brain networks after prolonged abstinence would be detected.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Although great progress had been made, abnormal functional connections in these networks in heroin users (HUs) were very limited. Moreover, brain regional and circuit-level recovery after prolonged abstinence had been observed in previous addiction studies [ 9 , 13 ]. Less is known about whether the brain recovery phenomenon in large-scale brain networks after prolonged abstinence would be detected.…”
Section: Introductionsupporting
confidence: 54%
“…Recent studies had revealed the functional disruptions of these networks in heroin addiction, such as stronger connectivity between SN and ECN during resting-state, and stronger activation in the DMN when exposed to the heroin-related cue. Meanwhile, the altered connections among key nodes distributed in the SN, ECN, and DMN were correlated with craving or duration of heroin use [ 6 - 9 ]. Besides, similar dysregulated interactions were also in nicotine addiction.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Neuroimaging studies have shown that anatomical abnormalities and dysfunctions in some brain regions, 3–5 like the prefrontal cortex (PFC), striatum, insula and thalamus, are related to reward processing and impaired cognitive control 6 in patients and animals with OUD or substance use disorders (SUD). Moreover, associations between clinical outcomes (craving or behaviour improvement) and neuroimaging measures after protracted abstinence in OUD were demonstrated by recent longitudinal studies, 7 revealing potential brain recovery after protracted abstinence. However, these studies have mainly concentrated on brain abnormalities based on group-level differences (eg, OUD vs healthy controls (HCs) or preprotracted/postprotracted abstinence), providing incomplete data since individual differences exist in symptomatic or behavioural improvement, especially in craving improvement during protracted abstinence in SUD.…”
Section: Introductionmentioning
confidence: 90%
“…Previous longitudinal studies in methamphetamine addiction observed the recovery of DA function in the striatum after prolonged abstinence. We also found that the cortical thickness in prefrontal regions in heroin and cocaine addiction users tended to be normal accompanied by decreased craving scores after prolonged abstinence (He et al ., 2018 ; Yang et al ., 2022 ). The increased functional connectivity of the midbrain-cortical circuits shown after 10 months' abstinence indicated partial brain recovery of impaired function during abstinence (Xu et al ., 2021 ).…”
Section: Brain Recovery After Prolonged Abstinence In Addictionmentioning
confidence: 99%